2015
DOI: 10.31018/jans.v7i2.712
|View full text |Cite
|
Sign up to set email alerts
|

Effect of waterlogging tolerance in wheat (Tritium aestivum L.) at ear emergence stage on growth, biochemical and yield parameters in sodic soil

Abstract: Globally more than one-third of the irrigated area is under waterlogging which limits our wheat production and out of which northern Indo-Gangetic plains of India alone had 2.5 million ha affected by irregular waterlogging. So, to meet out the food demand of ever-growing population we have to find some alternates to harness the potential of the waterlogged area. With this point of view this investigation was conducted to study the changes in growth and biochemical behavior of wheat due to waterlogging at ear e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Several authors observed decreases in chlorophyll content with waterlogging. At the emergence stage, a 10-day’s stress induced chlorophyll reductions between 15 and 33% in four wheat genotypes [ 93 ]. At the tillering stage, reductions from 41% to 61% were observed in six wheat varieties subjected to 28 days waterlogging [ 80 ].…”
Section: Plant Responses To Waterloggingmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors observed decreases in chlorophyll content with waterlogging. At the emergence stage, a 10-day’s stress induced chlorophyll reductions between 15 and 33% in four wheat genotypes [ 93 ]. At the tillering stage, reductions from 41% to 61% were observed in six wheat varieties subjected to 28 days waterlogging [ 80 ].…”
Section: Plant Responses To Waterloggingmentioning
confidence: 99%
“…The ability to maintain membrane integrity under stressful conditions ensures cellular compartmentalization and the functioning of metabolic processes, being determinant to protoplasmic tolerance [ 83 ]. Waterlogging, as well as other biotic and/or abiotic stresses, can lead to changes at the membrane level, with structural impacts that affect membrane permeability, assessed through increased electrolyte leakage from cells [ 83 , 99 , 100 , 101 ], that may reflect severe membrane damage and low survival ability [ 93 , 102 ]. Therefore, membrane stability is frequently used as an indicator of tolerance or susceptibility to environmental stresses [ 83 , 103 ].…”
Section: Plant Responses To Waterloggingmentioning
confidence: 99%